Electroless copper deposition on (3-mercaptopropyl)triethoxysilane-coated silica and alumina nanoparticles - Mondin, Giovanni; Lohe, Martin R.; Wisser, Florian M.; Grothe, Julia; Mohamed-Noriega, Nasser; Leifert, Annika; Doerfler, Susanne; Bachmatiuk, Alicja; Ruemmeli, Mark H.; Kaskel, Stefan (Electrochimica Acta, 2013)
A new approach for fabricating copper coated silica and alumina nanoparticles by a mercaptosilane-based coating and subsequent electroless plating is reported. Mercaptosilane covalently binds to the particle surface via hydrolysis and condensation reactions, while the mercapto group promotes a selective metal deposition during the electroless plating process due to its high affinity towards metal ions. The combination of an organic-based treatment process with electroless plating ensures a scalable and homogeneous metal coating strategy. Moreover, no further activation and sensitization steps with palladium-based solutions are required, thus overcoming the high costs and complexity of the state of the art metallization procedures. Metal coated nanoparticles synthesized with this procedure show a uniform and conformal coating and are particularly well suited for the production of metal matrix composites. The metal coating facilitates the integration and compatibility of the ceramic particles within the metal matrix, and can act as a barrier layer preventing undesired reactions between the two phases. Such composites are potential components for a wide range of applications including components for the automotive and aerospace industries, electromagnetic interference shielding, cutting tools, reinforced electrodes and coatings. © 2013 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Copper; Electroless plating; Metal coating; Metal matrix composites; Nanoparticles